Workload Measurement Using the Cardiovascular Load Method and Defense Research Agency Workload Scale - Kurniawan, Dicky; Akmal, Syarifah; Sayuti, Muhammad (International Journal of Engineering, Science and Information Technology, 2024)
Workload is a collection of tasks set to be completed within a specific time. The workload can be broken down into "qualitative" (too much or too little) or "quantitative" (too much or too little), which occurs when people are unable to complete tasks or if they do not utilize the abilities they have in achieving a particular job. This study aimed to determine the workload of workers engaged in the sale of fresh or cut chicken meat. Cardiovascular Load is an estimate to determine the classification of workload based on the increase in work pulse compared to the maximum heart rate. The Defense Research Agency Workload Scale (DRAWS) method is a multidimensional technique that involves participants through subjective questions and assessments consisting of four workload dimensions: input demand, central demand, output demand, and time pressure. The results showed that the workload pulse using Cardiovascular Load, the level of fatigue based on workload obtained at the chicken slaughter station by worker 1 was 44.77%, and worker 2 was 41.11% with the category of improvement needed. At the chicken cleaning station, worker 1 was 44.13%, and worker 2 was 47.43%, with the category of needed improvement. At the chicken cutting station, worker 1 was 43.73%, and worker 2 was 45.85%, with the category of needed improvement. The study's DRAWS method results showed that at the chicken slaughtering station, worker 1 was 84.25%, and worker 2 was 87.05% with the overload category. At the chicken cleaning station, worker 1 was 86.75%, and worker 2 was 84.20% with the overload category. At the chicken cutting station, worker 1 was 85.75%, and worker 2 was 81.30%, with the overload category. This means that six respondents felt a high mental burden, so improvements are needed to reduce the impact of the cognitive workload of workers. The upgrades provided include the provision of chairs around the work area, especially at the chicken slaughtering station, so that workers can sit and rest for a moment to reduce the physical workload experienced by workers.